Expressões algebricas
a) 32 + { -15 - [ 14 - (-5 ) ] -12 =
b) { 14 - (-2 ) + [ ( -5 ) - ( - 39) } =
c) 9 + ( - 23 ) - { 60 + [ - 11 + ( - 11 ) - 13 ]}=
francaloja1:
Épara conferir esta valendo 3 pontos
Soluções para a tarefa
Respondido por
5
Olá,
Vamos lá,
a) =32 + { -15 - [ 14 - (-5 ) ] -12} =
= 32 +{ -15 - [ 14 + 5] -12}
= 32 +{ -15 - 19 - 12}
= 32 -46
= -14
b)= { 14 - (-2 ) + [ ( -5 ) - ( - 39) } =
= {14 + 2 + [ -5 +39}
={ 14 + 2 +34}
= 50
c)=9 + ( - 23 ) - { 60 + [ - 11 + ( - 11 ) - 13 ]}
= 9 - 23 - { 60 + [ -11 - 11 -13]}
= 9 - 23 - { 60 - 35}
= 9 -23 - 25
= -39
Vamos lá,
a) =32 + { -15 - [ 14 - (-5 ) ] -12} =
= 32 +{ -15 - [ 14 + 5] -12}
= 32 +{ -15 - 19 - 12}
= 32 -46
= -14
b)= { 14 - (-2 ) + [ ( -5 ) - ( - 39) } =
= {14 + 2 + [ -5 +39}
={ 14 + 2 +34}
= 50
c)=9 + ( - 23 ) - { 60 + [ - 11 + ( - 11 ) - 13 ]}
= 9 - 23 - { 60 + [ -11 - 11 -13]}
= 9 - 23 - { 60 - 35}
= 9 -23 - 25
= -39
Respondido por
2
Ola Fran
a)
32 + (-15 - (14 - (-5)) - 12
32 + (-15 - 19) - 12
32 - 34 - 12 = 20 - 34 = -14
b)
(14 - (-2) + ((-5) - (-39)))
14 + 2 + (-5 + 39) = 16 + 34 = 50
c)
9 + (-23) - (60 + (-11 + (-11) - 13))
9 - 23 - (60 - 22 - 13) = 9 - 23 - 25 = -39
.
a)
32 + (-15 - (14 - (-5)) - 12
32 + (-15 - 19) - 12
32 - 34 - 12 = 20 - 34 = -14
b)
(14 - (-2) + ((-5) - (-39)))
14 + 2 + (-5 + 39) = 16 + 34 = 50
c)
9 + (-23) - (60 + (-11 + (-11) - 13))
9 - 23 - (60 - 22 - 13) = 9 - 23 - 25 = -39
.
Perguntas interessantes